Characterization of cucumber mosaic virus (CMV) causing mosaic symptom on Catharanthus roseus (L.) G. don in Malaysia - Mamat, Mazidah; Yusoff, Khatijah; Hashim, Habibuddin; Tan, Yee How; Lau, Wei Hong (Universiti Putra Malaysia Press, 2012)
A cucumber mosaic virus (CMV) isolate, causing leaf mosaic and distortion, malformed flowers or colourbreaking on the petals of Catharanthus roseus in Serdang, Selangor, Malaysia, was identified and designated as Malaysian periwinkle isolate (CMV-MP). The virus was spherical in shape with the size of 28.6 Â± 0.48 nm in diameter with a central core. It was mechanically transmitted to various test plants which produced typical symptoms of CMV infection. The coat protein (CP) gene of the virus was amplified using reverse transcriptasepolymerase chain reaction (RT-PCR) and cloned in Escherichia coli using TOPO-TA vector. A single open reading frame of 657 nucleotides, potentially encoding for 218 amino acids was sequenced. A comparison with the CP genes of other CMV isolates indicated that CMV-MP shared 100% sequence homology to the CP gene sequence of C. roseus isolate of CMV in India. This is the first aetiology report on C. roseus in Malaysia showing natural mosaic disease symptoms supported with the nucleotide sequence analysis of the causal virus.